2013
DOI: 10.1039/c3nj00446e
|View full text |Cite
|
Sign up to set email alerts
|

Change in energy of hydrogen bonds upon excitation of 6-aminocoumarin: TDDFT/EFP1 study

Abstract: Density functional theory (DFT)/time dependent density functional theory (TDDFT) calculations combined with the effective fragment potential (EFP) method have been carried out to study the electronic structure and the excited state properties of 6-aminocoumarin (6AC) with five water molecules (6AC-(H 2 O) 5 complex). Ground-state geometries are optimized using DFT with the B3LYP functional combined with cc-pVDZ basis sets and transition energies are computed with the same basis set and functional. One intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 70 publications
(77 reference statements)
1
3
0
Order By: Relevance
“…According to the Δ r G aq,complex 0 value for the S 0 state in Table , ∼ 80% of C102 is present in the form of the C O ···H 2 O water complex in the neutral aqueous solution of the dye. The significant weakening of the amino complex and the strengthening of the oxo complex are in accordance with previous findings, though in other theoretical studies on C102 and similar molecules, weak complexes were reported also in the S 1 state with very long hydrogen bonds.…”
Section: Resultssupporting
confidence: 92%
“…According to the Δ r G aq,complex 0 value for the S 0 state in Table , ∼ 80% of C102 is present in the form of the C O ···H 2 O water complex in the neutral aqueous solution of the dye. The significant weakening of the amino complex and the strengthening of the oxo complex are in accordance with previous findings, though in other theoretical studies on C102 and similar molecules, weak complexes were reported also in the S 1 state with very long hydrogen bonds.…”
Section: Resultssupporting
confidence: 92%
“…The phenomenon of hydrogen bonding has been illustrious for its eminence in various fields like photo-physics, photochemistry and biochemistry. The systematic study of hydrogen bonds is much essential for comprehending the photo-physical properties of some organic molecules which is having electron donor and acceptor demeanor at ground and excited states [1][2][3][4]. The effective fragment potential (EFP) method furnish a polarizable QM-based force field to characterize the intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Out of two EFP methods EFP1 and EFP2, the original method EFP1, was initially evolved to explain aqueous solvation, by representing coulombic, induction and repulsive interactions [43][44]. Polarisable continuum model (PCM) is a solvation model for a Quantum Mechanical (QM) molecular system in which the solvent is symbolized as a continuum distribution of matter to describe the solvation effect on photo physical characteristics of biological and chemical chromophores at lower and higher energy states by implementing the DFT / TDDFT method [45][46].…”
Section: Introductionmentioning
confidence: 99%